Deep-sea Pasiphaeidae (Crustacea: Decapoda: Caridea) from off the Brazilian central coast between 11° and 22°S, collected by the Revizee Program - Tavares, Carolina R.; Cardoso, Irene A. (Zootaxa, 2006)
The family Pasiphaeidae is composed of seven genera, and only one of these genera, Leptochela, has been recorded from off Brazilian waters. From collections made during the Revizee Program — Central Score (between 11°–22°S and 200–2200m), four species are recorded for the first time from off the Brazilian coast: Pasiphaea merriami, Pasiphaea princeps, Parapasiphae cristata and Parapasiphae sulcatifrons.